SYSTEMATIC LITERATURE REVIEW : RECONSTRUCTION OF LAW REGULATION FOR WAQF LAND BY THE OWNERSHIP FOUNDATION - Indon Sinaga; A. Suwiyono; Siti Nurbaiti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The problems in the legal regulation of waqf land ownership by foundations lead to a lack of clarity on the legal status of waqf land ownership. This makes waqf land vulnerable to misuse or control by other parties. The weak role of Nadzir in the management of waqf land, causing many waqf lands to be neglected and unproductive. There is often overlapping authority between Nadzir and the foundation in the management of waqf land. This leads to inefficiency and conflict in the management of waqf land. This study aims to conduct a literature review on the development of waqf law in Indonesia, specifically regarding the legal regulation of waqf land ownership by foundations. The methodology employed in this literature review uses a systematic literature review approach, with samples comprising secondary data from journals accessed through the Crossref, Semantic Scholar, and Google Scholar databases. The identified journals were then selected based on inclusion criteria through the stages of research coding and quality assessment. Journals that passed the selection stage were analyzed descriptively. The results of the study yielded 14 journals that met the selection criteria. Based on the research findings, it can be concluded that the legal status of waqf land ownership needs clarification. This can be achieved by issuing legislation that explicitly regulates waqf land ownership. Additionally, the role of the Nadzir in managing waqf land should be strengthened. This can be done by providing training and guidance to the Nadzir on waqf land management. Furthermore, a clear mechanism should be established to resolve the overlapping authority between the Nadzir and foundations in managing waqf land. This can be accomplished by reconstructing legal regulations or internal foundation policies that govern the division of duties and authority between the Nadzir and the foundation concerning the foundation's waqf land assets